2013
DOI: 10.1038/jcbfm.2013.182
|View full text |Cite
|
Sign up to set email alerts
|

A New Role for Downstream Toll-like Receptor Signaling in Mediating Immediate Early Gene Expression during Focal Cerebral Ischemia

Abstract: To better understand the role of downstream Toll-like receptor (TLR) signaling during acute cerebral ischemia, we performed cDNA microarrays, on brain RNA, and cytokine arrays, on serum, from wild type (WT), MyD88 À / À and TRIF-mutant mice, at baseline and following permanent middle cerebral artery occlusion (pMCAO). The acute stress response pathway was among the top pathways identified by Ingenuity Pathway Analysis of microarray data. We used real-time polymerase chain reaction to confirm the expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 48 publications
(57 reference statements)
1
8
0
Order By: Relevance
“…Moreover, dual‐luciferase reporter assay confirmed that miR‐377 can directly regulate EGR2 expression by binding to its 3′UTR. Previous studies have demonstrated that EGR2 expression increased 10.9‐fold in the rats at 3 h after permanent middle cerebral artery occlusion (pMCAO) [Famakin et al, ]. Our data showed the expression of EGR2 was significantly increased in the MCAO rats and in the OGD‐treated microglia cells.…”
Section: Discussionsupporting
confidence: 65%
“…Moreover, dual‐luciferase reporter assay confirmed that miR‐377 can directly regulate EGR2 expression by binding to its 3′UTR. Previous studies have demonstrated that EGR2 expression increased 10.9‐fold in the rats at 3 h after permanent middle cerebral artery occlusion (pMCAO) [Famakin et al, ]. Our data showed the expression of EGR2 was significantly increased in the MCAO rats and in the OGD‐treated microglia cells.…”
Section: Discussionsupporting
confidence: 65%
“…Toll-like receptor 4 (TLR4)-mediated neuroinflammation figures centrally in a growing list of inflammatory and degenerative conditions of the central nervous system (CNS), including traumatic brain injury, ischemic stroke, hemorrhagic stroke, Alzheimer’s disease, multiple sclerosis, Parkinson’s disease, and amyotrophic lateral sclerosis [ 1 4 ]. These conditions share the common feature that endogenous molecules associated with injury, known as alarmins or danger-associated molecular patterns (DAMPs), converge upon TLR4 and initiate potentially deleterious inflammatory cascades [ 2 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…MyD88-signalling is an inducer of MMP-9 expression 27 , 28 . As MMPs are involved in mucosal fibrosis we determined the expression of tissue remodeling protease MMP-9 and the tissue inhibitor of metalloproteinases TIMP-1 in intestinal transplants by real-time PCR.…”
Section: Resultsmentioning
confidence: 99%
“…While Mmp9 expression was increased upon development of fibrosis we did observe a significant difference between the grafts from both genotypes. MyD88-signalling is a potent inducer of MMP-9 expression 27 , 28 . Likewise, GFP-Tg grafts transplanted into MyD88 −/− recipients yielded significantly lower expression levels than the MyD88 −/− grafts in GFP-Tg recipients.…”
Section: Discussionmentioning
confidence: 99%